Revoltas contra os europeus em Cantão (1895)
This is a diplomatic dispatch from the Portuguese Consulate in Canton, dated 19 June 1895, originating from the Secretariat of Foreign Affairs in Lisbon. The document, classified as Series A, reports on an alleged uprising against Europeans occurring in the interior of China, specifically within the province of Le-Tchouen. It notes that British and American missionaries are reportedly sheltered within the ‘Yamens’ of various Mandarins, while European ministers resident in Peking have already formally protested the incident. The dispatch acknowledges uncertainty regarding the veracity and scale of the revolt, stating that no concrete developments or official response have yet materialised as of the date of writing, and reserves the right to provide further updates should the situation evolve. The communication reflects contemporary diplomatic protocol and colonial-era terminology, offering insight into European diplomatic reporting mechanisms and perceptions of unrest within Qing China during the late 19th century. This transcription is suitable for scholarly analysis of imperial diplomacy, missionary safety, and intra-imperial tensions in East Asia circa 1895.
Keywords: American missionaries; British missionaries; Consul Reporting; Consulate Canton; Diplomatic Protest; East Asia colonial tensions; European missionaries; Historical Document Transcription; Imperial Missionary Networks; Intra-Imperial Safety; Keyword Refinement; Le Tchouen uprising; Mandarins’ protective role; Missionary Sheltering; Official Communication Channels; Peking ministers; Portuguese diplomatic dispatch; Qing China unrest; Scholarly Analysis; Secretariat of Foreign Affairs; Series A classification; Transcription; Yamens of Mandarins; early modern East Asia